Vaginal vault prolapse and recurrent surgery: A nationwide observational cohort study - Malin Brunes; Marion Ek; Anna Drca; Marie Söderberg; Ida Bergman; Anna Warnqvist; Ulrika Johannesson (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction In surgical repair of pelvic organ prolapse the recurrence rate is about 30% and the importance of apical support was recently highlighted. In surgical randomized controlled studies, the external validity can be compromised because the surgical outcomes often depend on surgical volume. Therefore, we sought to study outcomes of surgical treatment in patients with vaginal vault prolapse in a nationwide setting with a variety of surgical volumes. Material and methods This is a nationwide cohort study. All patients with a vaginal vault prolapse undergoing surgery, between January 1, 2015 and December 31, 2018, were identified from the Swedish National Quality Register of Gynecological Surgery, GynOp. The primary outcome was the frequency of recurrent pelvic organ prolapse surgery within 2 years postoperatively. Secondary outcomes included patient‐reported vaginal bulging, operative time, estimated blood loss and 1‐year postoperative complications. Results In 1812 patients with vaginal vault prolapse, 538 (30%) had a sacrospinous ligament fixation (SSLF) with graft, 441 (24%) underwent SSLF without graft, and 200 (11%) underwent minimally invasive sacrocolpopexy (SCP) or sacrocervicopexy (SCerP). A significantly higher proportion of patients undergoing recurrent pelvic organ prolapse surgery was seen in SSLF without graft than in SSLF with graft (adjusted odds ratio [aOR] 2.2, 95% CI 1.4–3.6). Patient‐reported sensation of vaginal bulging 1 year after surgery was higher in the SSLF group without graft than in the SSLF group with graft (aOR 1.9, 95% CI 1.3–2.8) and in the SCP/SCerP group (aOR 2.0, 95% CI 1.1–3.4). Finally, we found a significantly higher rate of complications 1 year after surgery in SSLF without graft (aOR 2.3, 95% CI 1.2–4.2) and in SSLF with graft (aOR 2.2, 95% CI 1.2–4.2) compared with SCP/SCerP. Conclusions In patients with vaginal vault prolapse, SSLF without graft was associated with a higher frequency of recurrent pelvic organ prolapse surgery compared with SSLF with graft, and a higher subjective relapse rate compared with SCP/SCerP and SSLF with graft. Additionally, the complication rate 1 year after primary surgery was higher in SSLF both with and without graft than in SCP/SCerP.